Transmediality and Transmedia Narratives in the age of Interactive Digital Communication: The Case of Newspapers (Docentes 2.0 Journal, 2024)
Transmediality is the ability of a story or narrative to expand across multiple platforms and media. The research aimed to analyze the adaptation and transformation of narratives in interactive digital communication, with a specific focus on the newspaper industry. Given the small number of research in this field, we started with a qualitative approach that allowed an exhaustive review of the existing literature to contextualize the topic, identify key concepts, and summarize the results of previous research. The compilation of research, theories, and concepts related to transmediality and transmedia narratives. It highlights that the media are currently immersed in transmediality in response to the growing demand for an interactive digital communication experience by users. To achieve this, they are adopting transmedia strategies. As a result, this study contributes to the debate as a basis for understanding the relevance of transmediality in journalism, particularly in the newspaper industry. In conclusion, it is identified how applying transmedia approaches can significantly improve interactive digital communication today. Likewise, the contribution to the research gap in this field is achieved and contributes to the literature and the disciplinary field.
Keywords: Transmediality; narratives; journalism; interactive; adaptation